2018
DOI: 10.1002/jia2.25214
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the adoption of lopinavir/ritonavir oral pellets for HIV‐positive children in Zimbabwe

Abstract: IntroductionHeat‐stable lopinavir/ritonavir (LPV/r) oral pellets were developed to overcome challenges with administration and storage experienced with previously available tablet and syrup forms of LPV/r prescribed to paediatric HIV patients. We report on the adoption of LPV/r pellets for infants living with HIV in the public sector antiretroviral therapy (ART) programme in Zimbabwe.MethodsInfants aged three months to three years who had been prescribed a LPV/r‐based regimen (including ART‐naïve patients) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“… 7 Caregivers in our study reported a preference for granule formulations compared with other available ART formulations for infants. This aligns with another study from Zimbabwe that found caregivers generally preferred LPV/r in the form of granules over liquid, 10 most likely due to granules masking the unpleasant medication taste. Previous research has stated that palatability is one of the main challenges with paediatric medications, leaving caregivers struggling to administer bitter-tasting medications.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 7 Caregivers in our study reported a preference for granule formulations compared with other available ART formulations for infants. This aligns with another study from Zimbabwe that found caregivers generally preferred LPV/r in the form of granules over liquid, 10 most likely due to granules masking the unpleasant medication taste. Previous research has stated that palatability is one of the main challenges with paediatric medications, leaving caregivers struggling to administer bitter-tasting medications.…”
Section: Discussionsupporting
confidence: 89%
“…The Zimbabwe LPV/r study also recommended appropriate counselling to ensure caregivers can confidently administer granules. 10 Ensuring appropriate preparation, administration and dosing of RAL granules in neonates is essential for preventing the development of HIV drug resistance to RAL, which may impact the effectiveness of the DTG-based regimens that are currently the recommended first-line regimens for infants and children ≥4 weeks of age. 4 HCWs requested that the trainings are standardised and that they are trained directly by trainers, as opposed to having previously trained HCWs teaching them how to use RAL.…”
Section: Open Accessmentioning
confidence: 99%
“…Of note, viral suppression rates have been somewhat lower in younger children initiating ART, for whom administration of and adherence to LPVr pellets appears to be more challenging. Sites using the formulation as part of routine care programs report similar viral suppression rates as with LPVr syrup, due to persisting administration and palatability issues 17 .…”
Section: Current Reality and Ongoing Developments In Paediatric Antiretroviral Treatment For Hivmentioning
confidence: 99%
“…55,57 In addition, attempts have been made to develop "mini-tab sprinkles" (pellets stored in capsules) as an oral solid formulation to replace syrups. 58,59 For particularly serious infections, such as soil-transmitted helminths and HIV, clinical trials are sometimes conducted during drug development to ensure pediatric acceptability of pellet capsules (sprinkle capsules) and chewable tablets. 60,61…”
Section: Formulationsmentioning
confidence: 99%